Neural Networks with Keras Cookbook : Over 70 recipes leveraging deep learning techniques across image, text, audio, and game bots /: Over 70 recipes leveraging deep learning techniques across image, text, audio, and game bots. (2019) - Ayyadevara, V Kishore
No abstract available